Estudio de prefactibilidad para la instalación de un marketplace de frutas y verduras en el área de Lima Metropolitana - Mallqui Pilco, Junior Diego (2022)
The project proposes a market opportunity based on two trends. The first of these is a healthy consumption trend that has been growing over the last 10 years and has been further reinforced by the issue of octagons in products, since the Peruvian consumer reviews the nutritional information of their products before making the decision to buy; Likewise, the perception of a healthy diet by the consumer is based on a diet that includes fruits and vegetables. The second variable to consider is the purchase behavior of the Peruvian consumer, since the Peruvian buyer believes that technology improves their lives and 61% of the population expects a simpler purchase process according to their interests thanks to technology. In relation to the variables presented, a fruit and vegetable marketplace with a savings functionality is proposed as an implementation proposal so that the consumer chooses what he wants to buy according to the budget he manages for this purchase, in this way we make his process of purchase according to your interests. In the first chapter, the problem of the situation based on the variables of healthy eating and purchasing behavior is explained. Likewise, the objectives and the hypothesis of the research are established, as well as the methodology to be used to support the hypothesis. In the second chapter, the market study is carried out in which the characteristics of the service to be offered are discussed, a digital platform that connects the bidders, who will be known as partners for this project, with the final consumers who will be the users of the platform. Likewise, the macro and micro analysis of the environment is detailed, and the value proposition is presented through a CANVAS business model. Finally, the real demand of the project is determined, which amounts to a total of 25,150 people for the year 2022 with a purchase behavior of S/ 16.1 per transaction, achieving a projected total of 603,595 transactions for the 2nd year and 1 197,971 at the end of the project's 5-year life. In the third chapter, the macro and micro location of the service is determined through a confrontation matrix and a ranking of factors, obtaining the San Isidro district in Metropolitan Lima as the ideal location. In the fourth chapter, it is determined that the dimensioning of the service is defined by the market size relationship due to the behavior of consumption and purchase of the final customer. Likewise, it is determined that the transaction for the breakeven point is 481,535, 80% of the projected transactions, this occurs in the first year of the project. In the fifth chapter, the engineering of the project is developed. First, the macro and micro processes that are carried out within the company are detailed so that the operations can be carried out successfully. Secondly, the type of technology to be used is described, which in this case will be a SaaS developed by Staff Creativa, since it adjusts to the needs of the project and to an environment of high uncertainty. Then, topics to consider such as the quality of operations, customer service, environmental impact and service maintenance are explained. Finally, the proposed design for the platform and the implementation schedule are shared. In the sixth chapter, the business name of the company FRUTALY S.A.C is determined, as well as the requirement of 10 collaborators to start operations. The organization chart of the company is also shared. In the seventh chapter, the total investment of the project is determined, which amounts to S/ 780,061.6 with financing of S/. 200,000 at 10% per year for 5 years with decreasing installments. Likewise, the viability of the project is determined with an economic NPV of S/ 1,674,129 and an IRR of 64%. Then, it is argued that the project has a recovery period of four years and an attractive benefit-cost ratio for investors of 13.15. Finally, it is determined that the commission per transaction has a high sensitivity index to the project since if it is negotiated, in favor of the supplier up to 90%, the project becomes unfeasible, that is, an Economic NPV equal to zero. Finally, in the eighth chapter, the social indicators are analyzed, which show a capital product ratio of S/ 90.92, which is an attractive amount for investors